Free-Space Laser Communications XXXI 2019
DOI: 10.1117/12.2506849
|View full text |Cite
|
Sign up to set email alerts
|

Pre-correction adaptive optics performance for a 10 km laser link

Abstract: For the next generation of very high throughput communication satellites, free-space optical (FSO) communication between ground stations and geostationary telecommunication satellites is likely to replace conventional RF links. To mitigate atmospheric turbulence, TNO and DLR propose Adaptive Optics (AO) to apply uplink pre-correction. In order to demonstrate the feasibility of AO pre-correction an FSO link has been tested over a 10 km range. This paper shows that AO pre-correction is most advantageous for low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Several experiments have been recently reported that demonstrated the technology feasibility for pre-compensation. These demonstrations took place either on a short path [1] or on a 10 km long horizontal path [2]. In both cases the representativeness of the line of sight is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Several experiments have been recently reported that demonstrated the technology feasibility for pre-compensation. These demonstrations took place either on a short path [1] or on a 10 km long horizontal path [2]. In both cases the representativeness of the line of sight is limited.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose TNO's optical feeder link adaptive optics (OFELIA) breadboard has been used. This experimental set-up has been built to test and verify the performance of Adaptive Optics pre-correction for optical feeder links [13,14]; see also Figure 6. It consists of an AO system, a Tx and Rx channel, and a focus camera to verify beam quality.…”
Section: Laboratory Experiments On Fiber Couplingmentioning
confidence: 99%
“…The presented OGT design is primarily driven by the BB84 protocol with a satellite service node orbiting at LEO. The BB84 approach is relativemature, for which subsystems have been demonstrated in laboratories or in relevant environments and even a comparable full end-to-end system has already been demonstrated [14,15]. With an overpass time of (only) a few minutes, a LEO satellite based service could offer near global coverage.…”
Section: Perspective On Qkd-node Earth Orbitmentioning
confidence: 99%
See 1 more Smart Citation
“…While classic AO pre-compensation relying on the downlink phase measurement is the most mature technique, having led to several experimental demonstration on the field , [1][2][3] several concepts to address the anisoplanatism issue can be found in the literature. The most efficient method would be to access to a measurement at PAA, for instance from a laser guide star (LGS) as originally proposed by Tyson.…”
Section: Introductionmentioning
confidence: 99%